Influence of Tiktok video content on youth people's online shopping intention for fashion items - Bui, Thi Ha; Le, Hau; Nguyen, Thi Mai Giang; Truong, Phan Bao Tran; Nguyen, Thi Ha Trang (Journal of Finance - Marketing Research, 2024)
This study delves into the influence of TikTok video content factors - Entertainment, Information, Usefulness, and Interaction - on the online purchase intention of fashion items among young consumers. Drawing upon the Integrated Theory of Planned Behavior, ABC model (Attitude, Behavior, Context) and Mobile Technology Acceptance Model framework, the research examines how these factors shape consumer behavior on popular social media platform. A quantitative approach was employed, utilizing survey data collected from 620 young respondents in Vietnam. The findings reveal that Entertainment, Information, Usefulness, and Interaction significantly impact online purchase intention, with Usefulness and Interaction emerging as the primary drivers. However, the study also acknowledges several limitations, including sample size constraints and potential biases inherent in self-reported data. Future research directions include longitudinal studies to explore the dynamic nature of consumer behavior on TikTok and comparative studies across different demographic groups to enhance generalizability. This study contributes valuable insights for marketers and advertisers seeking to leverage TikTok as a platform for engaging young consumers and driving online purchase behavior in the fashion industry.